A comparative evaluation of two electrode systems on continuous electrocoagulation of boron from produced water and mass transfer resistance. (April 2020) - Ezechi, Ezerie Henry; Isa, Mohamed Hasnain; Muda, Khalida; Kutty, Shamsul Rahman Mohamed
Highlights: Produced water is the largest wastestream of oil and gas exploration. Boron is a complex inorganic compound found in produced water. Aluminum has higher boron removal efficiency than iron electrode. Mass transfer driving force/affinity increased with increasing boron concentration. Boron mass transfer resistance correlated with film mass transfer. Abstract: This study evaluated the performance of aluminum and iron plate electrode systems on the continuous electrocoagulation of boron from produced water under varying conditions of retention time, initial concentration and electrode distance. The experimental data were validated for mass transfer resistance using the modified mass transfer factor (MMTF) model. Results show a similar trend for both electrode systems. Boron removal decreased from 78.7–60% for aluminum electrode and 67.3–53.3% for iron electrode with shortening retention time from 45 to 30 min.. Boron removal further decreased from 84 to 72.7 % for aluminum electrode and 76 to 61.3 % for iron electrode with increasing electrode distance from 0.5 cm to 1.5 cm. Analyses of the mass transfer resistance showed that the driving force (B) for boron mass transfer was concentration dependent and increased from 0.1037 to 0.4002 mg.g for aluminum electrode and 0.0445 to 0.1258 mg.g for iron electrode with increasing initial boron concentration from 5 to 15 mg/L. A similar trend was observed for the affinity between boron and the electroactive species. Analyses of boron mass transfer resistance related to the global and film mass transfer, and porous diffusion show that boron mass transfer resistance correlated to the film mass transfer for both electrode systems. Aluminum electrode system showed better performance for boron removal and higher mass transfer kinetics. This study clearly demonstrates that continuous electrocoagulation is a suitable alternative for boron removal from produced water.